PENDIDIKAN POLITIK DALAM RANGKA PENGUATAN PARTISIPASI POLITIK PEMUDA - haqqi, halifa; Dipokusumo, GPH (Lembaga Penelitian dan Pengabdian Masyarakat, 2020)
To encourage political participation, good political education is needed. Political education can target young people as agents of change that have much influence in political development. Therefore, it is important to provide political education in strengthening the political participation of Indonesian youth. This program aims to provide Political Education in Strengthening Youth Political Participation. The service program was held in a four-month time series, from January to April 2019. The socialization activities had been held in Mandan, Sukoharjo Regency on Saturday, April 21, 2019 for one day, attended by 34 young people. The method used in program was socialization and active discussions, and providing motivation for the participants, which was previously preceded by participant assessment activities. The socialization activity lasted for one day. The core material of socialization consists of (1) political introduction; (2) the importance of political participation; (3) youth's ideal actions in political participation. The members of this program were Youth Organization of Mandan , Sukoharjo. Through this program, it can be beneficial for: (1) youth and the general public, to get a picture of political education and positive political participation; (2) for regions, can develop regional potential, regional promotion, and regional development; (3) for tertiary institutions, as fulfillment of the Tri Dharma element of Higher Education.Â Keywords: Mandan, political education, youth.